Scaling-out sweetpotato and potato-led interventions to improve nutrition and food security in Tigray and Southern Nations, Nationalities, and Peoples’ Region - International Potato Center (2014)
A school-based model (school gardens and school feeding) is proving to be an eff ective strategy for disseminating nutrition and agriculture knowledge to farmers and infl uencing behavioural change at household level.